2020
DOI: 10.3389/fendo.2020.00614
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Plasma Protein-A2 Is Associated With Mortality in Patients With Lung Cancer

Abstract: Pregnancy-associated plasma protein-A (PAPP-A) and its homolog PAPP-A2 are enzymes that modulate the availability and mitogenic activity of insulin-like growth factor-I (IGF-I). PAPP-A has been implicated in numerous cancers but reports on PAPP-A2 in malignancy are non-existent. In a prospective observational study of 689 patients under suspicion of lung cancer, we examined levels of PAPP-A and PAPP-A2 and their relationship with mortality. Serum PAPP-A and PAPP-A2 concentrations were determined in pre-diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…Pappalysin 2 (PAPPA2) is a protein-encoding gene associated with several disorders, including Down's syndrome and HELLP syndrome. High expression of PAPPA2 is associated with mortality in lung cancer patients (26). Coincidentally, PAPPA2 is also associated with multiple immune cell types in gastric cancer, similar to the present study, in which PAPPA2 exhibited a positive correlation with activated mast cells, eosinophils, and activated memory CD4 T cells, and negative correlation with macrophage M0, macrophage M1, and CD8 T cells.…”
Section: Discussionsupporting
confidence: 88%
“…Pappalysin 2 (PAPPA2) is a protein-encoding gene associated with several disorders, including Down's syndrome and HELLP syndrome. High expression of PAPPA2 is associated with mortality in lung cancer patients (26). Coincidentally, PAPPA2 is also associated with multiple immune cell types in gastric cancer, similar to the present study, in which PAPPA2 exhibited a positive correlation with activated mast cells, eosinophils, and activated memory CD4 T cells, and negative correlation with macrophage M0, macrophage M1, and CD8 T cells.…”
Section: Discussionsupporting
confidence: 88%
“…The PAPP-As are responsible for the proteolytic cleavage of specific IGFBPs, through which they increase tissue concentrations of free IGF, which becomes available for receptor activation [17][18][19]. In breast cancer, an elevated serum PAPP-A has been shown to be associated with low recurrence-free and overall survival [20], and recently, we demonstrated that serum PAPP-A2 is higher in patients with lung cancer and predictive of all-cause mortality [13]. In 2015, stanniocalcin-1 (STC1) and -2 (STC2) were discovered as potent inhibitors of PAPP-A and PAPP-A2 [21,22].…”
Section: Introductionmentioning
confidence: 94%
“…Pregnancy-associated plasma protein-A (PAPP-A) and PAPP-A2 constitute the pappalysin family of metalloproteases [11]. They have been shown to play key roles in regulating IGF signaling in cancers [12][13][14][15][16]. The PAPP-As are responsible for the proteolytic cleavage of specific IGFBPs, through which they increase tissue concentrations of free IGF, which becomes available for receptor activation [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In literature, the involvement of PAPPA in cancer development and progression has been explored in multiple cancer types supporting its possible role as oncogene. PAPPA is overexpressed in ovarian cancer [6], lung cancer [7], breast cancer [8], Ewing sarcoma [9], testicular and prostate cancer [10] and hepatocellular carcinoma [11]. Moreover, evidences suggest that PAPPA activity promotes cancer proliferation, invasion, migration and metastasis [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%